A lentiviral sponge for miR-101 regulates RanBP9 expression and amyloid precursor protein metabolism in hippocampal neurons - Barbato, Christian; Pezzola, Silvia; Caggiano, Cinzia; Antonelli, Martina; Frisone, Paola; Ciotti, Maria Teresa; Ruberti, Francesca (Frontiers in Cellular Neuroscience, 2014)
Neurodegeneration associated with amyloid β (Aβ) peptide accumulation, synaptic loss, and memory impairment are pathophysiological features of Alzheimer's disease (AD). Numerous microRNAs regulate amyloid precursor protein (APP) expression and metabolism. We previously reported that miR-101 is a negative regulator of APP expression in cultured hippocampal neurons. In this study, a search for predicted APP metabolism-associated miR-101 targets led to the identification of a conserved miR-101 binding site within the 3’ untranslated region (UTR) of the mRNA encoding Ran-binding protein 9 (RanBP9). RanBP9 increases APP processing by β-amyloid converting enzyme 1 (BACE1), secretion of soluble APPβ (sAPPβ), and generation of Aβ. MiR-101 significantly reduced reporter gene expression when co-transfected with a RanBP9 3'-UTR reporter construct, while site-directed mutagenesis of the predicted miR-101 target site eliminated the reporter response. To investigate the effect of stable inhibition of miR-101 both in vitro and in vivo, a microRNA sponge was developed to bind miR-101 and derepress its targets. Four tandem bulged miR-101 responsive elements (REs), located downstream of the enhanced green fluorescence protein (EGFP) open reading frame and driven by the synapsin promoter, were placed in a lentiviral vector to create the pLSyn-miR-101 sponge. Delivery of the sponge to primary hippocampal neurons significantly increased both APP and RanBP9 expression, as well as sAPPβ levels in the conditioned medium. Importantly, silencing of endogenous RanBP9 reduced sAPPβ levels in miR-101 sponge-containing hippocampal cultures, indicating that miR-101 inhibition may increase amyloidogenic processing of APP by RanBP9. Lastly, the impact of miR-101 on its targets was demonstrated in vivo by intrahippocampal injection of the pLSyn-miR-101 sponge into C57BL6 mice. This study thus provides the basis for studying the consequences of long-term miR-101 inhibition on the pathology of AD.